High-strength and high-conductivity copper alloy with improved fatigue resistance and preparation method of high-strength and high-conductivity copper alloy

By controlling the content of Ni, Pb and P in high-strength and high-conducting copper alloys and optimizing their microstructure structure, the problem of insufficient performance of existing copper alloys under fatigue stress is solved, and strength, conductivity and fatigue resistance are achieved. Good match.

CN119410955APending Publication Date: 2025-02-11NINGBO BOWAY NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411170387.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing high-strength, high-conducting copper alloys are difficult to effectively cope with fatigue during long-term cycling service, which affects the reliability of electrical connectors.

Method used

By controlling the content of Ni, Pb and P in the copper alloy, adjusting the length and short diameter ratio of the grains in the microstructure of the longitudinal section, and controlling the crystal orientation aggregation degree of cross-section, the microstructure of the copper alloy is optimized.

Benefits of technology

The copper alloy strength, conductivity and fatigue resistance are achieved, with tensile strength ≥550MPa, conductivity ≥50% IACS, and the fatigue resistance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005009098280000071
    Figure BDA0005009098280000071
  • Figure BDA0005009098280000081
    Figure BDA0005009098280000081
  • Figure BDA0005009098280000091
    Figure BDA0005009098280000091
Patent Text Reader

Abstract

The invention discloses a high-strength and high-conductivity copper alloy with improved fatigue resistance. The high-strength and high-conductivity copper alloy comprises the following components in percentage by mass: 0.3-1.5% of Ni, 0.3-1.5% of Pb, 0.1-0.5% of P and the balance of Cu and inevitable impurities, in the microstructure of the longitudinal section of the copper alloy, the ratio l / s of the long diameter l to the short diameter s of crystal grains is 1.2-3. According to the invention, Ni, Pb, P and Cu are taken as main alloy elements, and the ratio of the long diameter l to the short diameter s of crystal grains in the microstructure of the longitudinal section of the copper alloy is controlled, so that the balance of strength and conductivity is achieved, good fatigue resistance is obtained, the tensile strength is greater than or equal to 550MPa, the conductivity is greater than or equal to 50% IACS, and the fatigue resistance is good. The copper alloy achieves good matching of strength, conductivity and fatigue resistance, and is suitable for various electric connectors, high-voltage electric appliance contacts, new energy automobile electronic parts and the like with precision machining requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloys, and in particular relates to a high-strength and high-conductivity copper alloy with improved fatigue resistance and a preparation method thereof. Background Art

[0002] As the core conductor material, advanced copper alloys are widely used in the electronic information industry and related fields. High-strength and high-conductivity copper alloys are mainly used in various electrical connectors, integrated circuit lead frames, high-speed rail transit contact wires, high-voltage electrical contacts, new energy vehicle electronic components, etc. Common materials include Cu-Fe-P series, Cu-Ni-Si series, and Cu-Cr-Zr series copper alloys.

[0003] Electrical connectors are components used to make and break circuits in various cutting-edge technology systems and large military and civilian systems. Their reliability will directly determine the performance of electronic and electrical equipment and the safety of system operation. With the rapid development of space technology, higher requirements are placed on the reliability of electrical connectors, which means that the materials used must not only have high strength and conductivity, but also need to cope with fatigue caused by long-term cyclic service to ensure the reliability of the components.

[0004] To address this problem, there is an urgent need to develop a high-strength and high-conductivity copper alloy with improved fatigue resistance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a high-strength and high-conductivity copper alloy with improved fatigue resistance and a preparation method thereof in view of the deficiencies in the prior art, thereby achieving a good match between the strength, conductivity and fatigue resistance of the copper alloy. The tensile strength of the copper alloy is ≥550MPa, the conductivity is ≥50%IACS, and the fatigue resistance is good.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a high-strength and high-conductivity copper alloy with improved fatigue resistance, the mass percentage composition of the copper alloy is Ni: 0.3-1.5%, Pb: 0.3-1.5%, P: 0.1-0.5%, and the remainder is Cu and inevitable impurities; in the microstructure of the longitudinal section of the copper alloy, the ratio l / s of the long diameter l to the short diameter s of the grain is 1.2-3.

[0007] Cu-Ni alloy belongs to an infinite continuous solid solution system, and its binary alloy has good plasticity. As the content of Ni in the copper alloy increases, the strength of the copper alloy also increases, but the cost is that it will have an adverse effect on the electrical conductivity. In order to make the copper alloy have both excellent strength and electrical conductivity, the content of Ni element needs to be controlled. If the content of Ni element is too low, the solid solution strengthening effect in the copper matrix is ​​insufficient, and the mechanical properties of the copper alloy cannot meet the requirements; if the Ni element is excessive, the effect of improving the mechanical properties of the copper alloy is not obvious, but the electrical conductivity of the copper alloy will be significantly reduced. Therefore, the Ni content in the copper alloy of the present invention is controlled at 0.3-1.5wt%.

[0008] The Pb element is almost not soluble in copper alloys, but for copper alloy materials that require precision processing, the appropriate addition of the Pb element can play a good role in improving the processing performance. This is because a small amount of Pb element added to the copper alloy will be distributed in the copper matrix in the form of particles, which plays a lubricating role during processing, thereby improving the processing performance. Excessive Pb will deteriorate the mechanical properties and electrical conductivity of the copper alloy; too low Pb cannot ensure that the particles are fully distributed in the copper matrix, which is not enough to effectively improve the processing performance. Therefore, the Pb content of the present invention is controlled at 0.30-1.5wt%.

[0009] As a good degassing and deoxidizing agent, P element is often added in small amounts during the casting of copper alloys to improve the fluidity of the copper melt and purify the melt. At the same time, a small amount of P element can be completely dissolved in the copper matrix to play a role in solid solution strengthening. After aging, it can also form compounds with Cu and Ni to precipitate, further enhancing the strengthening effect on the copper alloy. Under the premise of considering the above two factors, the P content in the copper alloy of the present invention is controlled at 0.1-0.5wt%.

[0010] In the microstructure of the longitudinal section of the copper alloy of the present invention, the ratio of the long diameter l to the short diameter s of the grains is l / s of 1.2 to 3. The process of macroscopic deformation of the copper alloy under load is manifested in the elongation and deformation behavior of the grains under the action of stress. When the grains are elongated to a certain extent in one direction, local stress concentration is prone to occur at the tip interface; especially when subjected to cyclical loads, the alloy has a higher tendency to fatigue failure, so it is necessary to control the degree of elongation of the grains, that is, the long and short diameters. The present invention controls the ratio of the long diameter l to the short diameter s of the grains in the microstructure of the longitudinal section of the copper alloy so that it falls within an appropriate range, which can effectively improve the fatigue resistance of the copper alloy.

[0011] Preferably, in the microstructure of the cross section of the copper alloy of the present invention, <111> noodle, <110> Face to face <100> Crystalline orientation concentration of the surface A 111 , A 110 , A 100 Satisfaction: A 111 / (A110 +A 100 )≥0.8. When copper alloy materials are subjected to tensile cyclic loads and produce fatigue, fatigue cracks often initiate in local areas with large stress concentrations. The inventors conducted a large number of tests on the tensile anisotropy of the alloy of the present invention and found that: <111> The critical shear stress of the surface is the smallest, <110> The critical shear stress of the surface is the largest. <100> The critical shear stress of the surface is between <111> Face to face <110> The smaller the critical shear stress, the easier it is for the alloy to slip dislocations, and the less likely it is for local stress concentration to occur due to the accumulation of dislocations. In order to further improve the fatigue resistance of the copper alloy, the present invention controls the microstructure of the cross section of the copper alloy. <111> noodle, <110> Face to face <100> The crystal orientation aggregation of the surface reduces <110> Face to face <100> Improve the surface at the same time <111> The preferred crystal orientation of the phase on the surface can obtain a copper alloy with better fatigue resistance.

[0012] In the copper alloy of the present invention, Pb mainly exists in the copper matrix in the form of particles. Unlike conventional hard particles, Pb particles have a lower hardness and are less likely to produce gaps in the copper matrix. When subjected to fatigue loads, cracks initiate later. By adjusting the size and quantity distribution of Pb particles, the fatigue resistance of the copper alloy can be further improved. Preferably, in the microstructure of the cross section of the copper alloy of the present invention, the number of Pb particles with a particle size of 100 nm to 5 μm is (5 to 20)×10 3 Pieces / mm 2 , to further improve the fatigue resistance of the copper alloy of the present invention.

[0013] Preferably, the copper alloy of the present invention also includes at least one element of Zn, Sn, Al, Mg, Mn, Si, Zr, Ag, Bi, Fe, Co and Cr in a total amount of 0.001-1.0%. Other solid solution elements can be added to the copper alloy of the present invention to further improve the strength of the copper alloy by solid solution strengthening. Some solid solution elements can also regulate the distribution of Ni-P precipitation phase and indirectly control the growth and distribution of Pb particles by affecting nucleation, such as Zn, Sn, Al, Mg, Mn, Zr, Ag, Bi and other elements. Precipitation strengthening elements such as Si, Fe, Co, Cr can be combined with other alloying elements to form different types of precipitation phases, and on the other hand, reduce the solid solution degree of Ni or P elements in the copper matrix, and play a precipitation strengthening effect while alleviating the decrease in conductivity. The total amount of the above elements should be controlled below 1.0wt%. Even if the added content is too high, it cannot produce further strengthening effects, but will reduce the conductivity of the copper alloy.

[0014] Preferably, the copper alloy of the present invention has a tensile strength of ≥550 MPa and an electrical conductivity of ≥50% IACS.

[0015] The preparation method of the copper alloy of the present invention comprises the following preparation process: melting and casting → hot working → first cold working → online heat treatment → second cold working → aging treatment → fine cold working, wherein the temperature of the online heat treatment is 700-900°C, and the heat treatment speed is ≥100mm / min; the second cold working and aging treatment are two processes as one cycle step, and the cycle step is repeated for several rounds.

[0016] Melting and casting can be carried out by continuous casting or semi-continuous casting, etc., and raw materials with low impurities or new materials are selected according to the alloy composition ratio to prepare ingots of certain specifications. It should be noted that in terms of the ratio of raw materials, due to the inevitable adhesion and volatilization in each process in the preparation process, the alloy composition of the copper alloy produced may not be completely consistent, but it is essentially the same.

[0017] Hot working heats the ingot to an initial temperature of 750-1000°C, and the processing method can be conventional processes such as hot rolling or extrusion. In addition, when the concentration of alloying elements is high, choosing an appropriate holding time can make the cast structure more uniform, and hot working can also be performed directly without holding.

[0018] The processing rates of the first cold working and the second cold working are 20-80% respectively, and the processing method can be selected from conventional processes such as cold rolling or cold drawing.

[0019] The temperature of the online heat treatment is controlled at 700-900°C, and the heat treatment speed is ≥100mm / min. The online heat treatment adopts a higher heat treatment temperature and heat treatment speed to play a role in directional recrystallization, so that alloying elements such as Ni, Pb, and P are fully dissolved into the copper matrix to form a saturated solid solution, and the grain morphology in the microstructure of the longitudinal section of the copper alloy is controlled by directional recrystallization. When the temperature of the online heat treatment is lower than 700°C, it is difficult to achieve the effect of recrystallization; when the temperature of the online heat treatment is higher than 900°C or the heat treatment speed is lower than 100mm / min, the tendency of the grains to coarsen laterally increases significantly, the average grain size increases, and it is difficult to obtain the desired grain length-to-short diameter ratio, and the strength and fatigue resistance will deteriorate. On the other hand, since the Pb content of the copper alloy of the present invention is relatively high, increasing the speed of the online heat treatment helps to prevent the abnormal growth of Pb particles at high temperatures, thereby reducing the tendency of cracks during subsequent processing.

[0020] The temperature of the aging treatment is 250-450°C, and the holding time is 0.5-10 hours. By setting the aging treatment with appropriate temperature and holding time, the supersaturated solid solution is evenly distributed in the copper matrix in the form of precipitation phase to play a strengthening role.

[0021] The processing rate of fine cold working is 10-50%, and the processing method can be selected from conventional processes such as cold rolling or cold drawing.

[0022] After the fine cold working is completed, the copper alloy of the present invention can be subjected to stress relief annealing to reduce the residual stress of the alloy. The temperature of the stress relief annealing is 200-400° C. and the holding time is 1 second to 10 hours.

[0023] Preferably, the processing rates of the first cold working and the second cold working are 10-25% respectively. For the copper alloy of the present invention, the processing rate of the cold working before the aging treatment should not be too large, so as to reduce the microstructure of the cross section of the copper alloy. <111> noodle, <110> Face to face <100> If the cold working pass processing rate before aging treatment is too low, the strengthening effect of subsequent aging treatment will be reduced, and the number of passes required will increase significantly, resulting in unnecessary energy consumption and reduced production efficiency; if the cold working pass processing rate before aging treatment is too high, <111> The crystal orientation concentration of the surface is reduced, which has an adverse effect on the fatigue resistance of the copper alloy.

[0024] Preferably, the cooling rate after the online heat treatment is controlled at above 100°C / min. Since the melting point of Pb is lower than that of the copper matrix, the Pb element is still distributed in liquid form at the recrystallization temperature of the copper alloy. After Pb is fully diffused through the directional solid solution effect of the online heat treatment, the Pb particles are quickly precipitated by using a larger cooling rate.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention uses Ni, Pb, P, and Cu as the main alloying elements, and controls the ratio of the long diameter l to the short diameter s of the grains in the microstructure of the longitudinal section of the copper alloy, thereby achieving a balance between strength and electrical conductivity, and at the same time achieving good fatigue resistance, achieving a tensile strength of ≥550MPa, a conductivity of ≥50%IACS, and good fatigue resistance of the copper alloy. The copper alloy of the present invention achieves a good match of strength, electrical conductivity, and fatigue resistance, and is suitable for various types of electrical connectors, high-voltage electrical contacts, and electronic components of new energy vehicles with precision processing requirements. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below with reference to the embodiments.

[0027] The present invention provides 16 embodiment alloys and 4 comparative example alloys in total, and the chemical compositions of the alloys are shown in Table 1.

[0028] Taking the preparation of copper alloy wire as an example, the process flow of preparing the alloy wire in each embodiment is: melting → extrusion → primary cold drawing → online heat treatment → secondary cold drawing → aging treatment → fine drawing → stress relief annealing, and finally a wire sample with a diameter of 3 mm is obtained, which specifically includes the following steps:

[0029] 1) Melting and casting: Prepare the raw materials and proportion the ingredients according to the alloy chemical composition in Table 1, use an induction furnace for smelting, and cast after the composition meets the requirements and is fully degassed and deslaged at a temperature of 1200°C;

[0030] 2) Extrusion: initial extrusion temperature 850°C, processing rate 90%, followed by cooling to room temperature;

[0031] 3) Primary cold drawing: After the extruded billet is sheared and straightened, it is cold drawn. The cold drawing process parameters are shown in Table 2;

[0032] 4) Online heat treatment: The wire after the primary cold drawing is subjected to online heat treatment. The heat treatment process parameters are shown in Table 2;

[0033] 5) Secondary cold drawing: cold drawing is performed on the wire after online heat treatment. The cold drawing process parameters are shown in Table 2;

[0034] 6) Aging treatment: The wire after secondary cold drawing is subjected to aging treatment at a temperature of 350°C and a holding time of 6 hours;

[0035] 7) Fine drawing: After cleaning the wire after aging treatment, fine drawing is performed, and the fine drawing processing rate is 10-50%;

[0036] 8) Stress relief annealing: The wire after fine drawing is subjected to stress relief annealing at a temperature of 300°C and a holding time of 4 hours;

[0037] The difference between Comparative Examples 1 to 3 and Examples 1 to 16 is that the compositions thereof are not within the composition range of the copper alloy of the present invention.

[0038] The difference between Comparative Example 4 and Example 3 is that the heat treatment speed of the online heat treatment is lower than 100 mm / min.

[0039] The microstructure, tensile strength, electrical conductivity, fatigue resistance, etc. of the wires prepared from the alloys of Examples 1 to 16 of the present invention and the alloys of Comparative Examples 1 to 4 were evaluated according to the methods specified in the relevant national and industry standards. The test and measurement methods for each evaluation item are as follows. The evaluation results are shown in Table 3.

[0040] Tensile strength: The room temperature tensile test is carried out on an electronic universal mechanical properties testing machine in accordance with GB / T 228.1-2021 Metallic Materials Tensile Test Part 1: Room Temperature Test Method.

[0041] Conductivity: The conductivity of the sample is tested using GB / T 351-2019 Metal Material Resistivity Measurement Method.

[0042] Fatigue resistance: Ten tensile specimens with a length of 200 mm were selected along the axial direction of the sample, and a stress of 5% strain was used as the test load. The load was repeatedly applied and unloaded. The specimens were observed after 1000 cycles. If there was no obvious crack on the surface, it was evaluated as ○, if there was a crack with a length of more than 1 mm, it was evaluated as △, and if there was a break, it was evaluated as ×.

[0043] Grain morphology: The EBSD method was used to observe the longitudinal section of the sample in a viewing area of ​​100μm×100μm. The boundaries with an orientation of more than 5° were regarded as grain boundaries. The length values ​​of the long axis and short axis of each grain were observed and measured. The long axis length of the grain was defined as the long diameter l, and the short axis length of the grain was defined as the short diameter s. The ratio l / s of all the long diameters l to the short diameters s in the viewing area was calculated and the average value was taken.

[0044] Crystal orientation concentration: Cut the test sample along the sample axis and observe the cross section of the sample using the EBSD method. The surface with an angle of less than 10 degrees from the opposite orientation is defined as the corresponding orientation surface. <111> noodle, <110> Face to face <100> The percentage of the area of ​​face-oriented grains to the total area is defined as <111> noodle, <110> Face to face <100> Crystalline orientation concentration of the surface A 111 , A 110 , A 100 , and calculate A 111 / (A 110 +A 100 ) value.

[0045] Pb particle distribution: A scanning electron microscope was used to observe the cross-sectional microstructure and morphology of the sample from the axial direction. Ten viewing areas were randomly selected and the number of Pb particles with a particle size of 100 nm to 5 μm per unit area was calculated, where the size of the Pb particle was the length of the longest line segment passing through the particle.

[0046] According to the evaluation results shown in Table 3, within the scope of the present invention, the microstructures of the samples of Examples 1 to 16 of the present invention achieve a tensile strength ≥ 550 MPa and a conductivity ≥ 50% IACS, while having good fatigue resistance, achieving a good match of strength, conductivity and fatigue resistance.

[0047] Among them, Example 9 and Example 12 respectively use relatively higher pass processing rates in the first cold drawing and the second cold drawing, which reduces the processing passes, resulting in a large deviation in the crystal orientation aggregation degree in the microstructure. Although the fatigue resistance can still meet the requirements, the surface microcracks of the samples after testing are significantly more than those of the samples in other embodiments; Example 13 and Example 14 use a relatively small cooling rate after online heat treatment, resulting in the aggregation of Pb particles distributed in liquid state, which cannot be fully diffused. The number of Pb particles of 100nm to 5μm observed per unit area is significantly reduced. Although the fatigue resistance can still meet the requirements, the surface microdefects of the samples after testing are more than those of the samples in other embodiments.

[0048] In the samples of Comparative Examples 1 to 3, since the contents of elements such as Ni, Pb, and P exceeded the scope of the present invention, the strength and conductivity were significantly affected; in Comparative Example 4, the grain morphology in the microstructure of the longitudinal section of the alloy was not controlled, and the ratio l / s of the long diameter l to the short diameter s of the grain was not within the scope of the present invention, resulting in poor fatigue resistance.

[0049] Table 1 Chemical composition of alloys of Examples and Comparative Examples

[0050]

[0051]

[0052] Table 3 Microstructure and properties of embodiments and comparative examples

[0053]

Claims

1. A high-strength and high-conductivity copper alloy with improved fatigue resistance, characterized in that: The copper alloy has a mass percentage composition of Ni: 0.3-1.5%, Pb: 0.3-1.5%, P: 0.1-0.5%, and the balance is Cu and inevitable impurities; in the microstructure of the longitudinal section of the copper alloy, the ratio l / s of the long diameter l to the short diameter s of the grain is 1.2-3.

2. The high-strength and high-conductivity copper alloy with improved fatigue resistance according to claim 1, characterized in that: In the microstructure of the copper alloy cross section, <111> noodle, <110> Face to face <100> Crystalline orientation concentration of the surface A 111 , A 110 , A 100 Satisfaction: A 111 / (A 110 +A 100 )≥0.

8.

3. The high-strength and high-conductivity copper alloy with improved fatigue resistance according to claim 1, characterized in that: In the microstructure of the cross section of the copper alloy, the number of Pb particles with a particle size of 100nm to 5μm is (5 to 20)×10 3 Pieces / mm 2 .

4. The high-strength and high-conductivity copper alloy with improved fatigue resistance according to claim 1, characterized in that: The copper alloy also includes at least one element of Zn, Sn, Al, Mg, Mn, Si, Zr, Ag, Bi, Fe, Co and Cr in a total amount of 0.001 to 1.0% by mass percentage.

5. The high-strength and high-conductivity copper alloy with improved fatigue resistance according to any one of claims 1 to 4, characterized in that: The copper alloy has a tensile strength of ≥550 MPa and an electrical conductivity of ≥50% IACS.

6. The method for preparing a high-strength and high-conductivity copper alloy with improved fatigue resistance according to any one of claims 1 to 5, characterized in that: The preparation process is: melting and casting → hot working → first cold working → online heat treatment → second cold working → aging treatment → fine cold working, the temperature of the online heat treatment is 700-900°C, and the heat treatment speed is ≥100mm / min; the second cold working and aging treatment are two processes as one cycle step, and the cycle step is repeated for several rounds.

7. The method for preparing a high-strength and high-conductivity copper alloy with improved fatigue resistance according to claim 6, characterized in that: The initial temperature of the heat treatment is 750-1000°C, the temperature of the aging treatment is 250-450°C, and the insulation time is 0.5-10h.

8. The method for preparing a high-strength and high-conductivity copper alloy with improved fatigue resistance according to claim 6, characterized in that: The processing rates of the first cold working and the second cold working are 10-25% respectively.

9. The method for preparing a high-strength and high-conductivity copper alloy with improved fatigue resistance according to claim 6, characterized in that: The cooling rate after the online heat treatment is controlled to be above 100°C / min.

10. The method for preparing a high-strength and high-conductivity copper alloy with improved fatigue resistance according to claim 6, characterized in that: After the fine cold working is completed, the copper alloy is subjected to stress relief annealing, wherein the stress relief annealing temperature is 200-400° C. and the heat preservation time is 1 second to 10 hours.